Grades da pele: um processo de criação em dança a partir de experiências familiares em situação de cárcere - SILVA, Jeniffer Patrícia Moura da (2022)
This is a memorial of a choreographic work that deals with my experience as a relative of a detainee, due to the difficulties of experiencing prison and how dance helps in this process. In this way, it presents a process about self-care through dance, as well as, reports how these lived experiences became propellers of a scenic poetics. I named the methodological approach created for this research-creation as choreovisite, in addition to visits to the physical space of the prison, I carry out reports of experiences, a process of choreographic composition and a bibliographic study about the context of the prison through authors such as Michel Foucault ( 2012), Fábio Godoi and Rafael Mallart (2017); on Creative process in dance and politics through authors such as André Lepecki (2012), Helena Katz and Christine Greiner (2012) who outline their theoretical experiences through dance in relationships with the world, without a kind of rule or prescriptions; and João de Jesus Paes Loureiro's (2007) understanding of semiotic conversion to think about how to create dance through a daily experience. As a result, I can say that this whole process is based on the continuity of movements, gestures and reframing of experiences and, therefore, it contributes to self-care in a difficult life experience and, in addition, I realize that, like life processes, dance processes remain in an unfinished state.